Investigating the role of typhoon-induced waves and stratospheric hydration in the formation of tropopause cirrus clouds observed during the 2017 Asian monsoon - A. K. Pandit; J.-P. Vernier; J.-P. Vernier; T. D. Fairlie; K. M. Bedka; M. A. Avery; H. Gadhavi; M. Venkat Ratnam; S. Dwivedi; K. Amar Jyothi; F. G. Wienhold; H. Vömel; et al. (Atmospheric Chemistry and Physics, 2024)
We investigate the formation mechanism of a tropopause cirrus cloud layer observed during the Balloon measurement campaigns of the Asian Tropopause Aerosol Layer (BATAL) over Hyderabad (17.47° N, 78.58° E), India, on 23 August 2017. Simultaneous measurements from a backscatter sonde and an optical particle counter on board a balloon flight revealed the presence of a subvisible cirrus cloud layer (optical thickness ∼ 0.025) at the cold-point tropopause (temperature ∼ −86.4 °C, altitude ∼ 17.9 km). Ice crystals in this layer are smaller than 50 µm with a layer mean ice crystal number concentration of about 46.79 L−1. Simultaneous backscatter and extinction coefficient measurements allowed us to estimate the range-resolved extinction to backscatter coefficient ratio (lidar ratio) inside this layer with a layer mean value of about 32.18 ± 6.73 sr, which is in good agreement with earlier reported values at similar cirrus cloud temperatures. The formation mechanism responsible for this tropopause cirrus is investigated using a combination of three-dimensional back trajectories, satellite observations, and ERA5 reanalysis data. Satellite observations revealed that the overshooting convection associated with a category 3 typhoon, Hato, which hit Macau and Hong Kong on 23 August 2017, injected ice into the lower stratosphere. This caused a hydration patch that followed the Asian summer monsoon anticyclone to subsequently move towards Hyderabad. The presence of tropopause cirrus cloud layers in the cold temperature anomalies and updrafts along the back trajectories suggested the role of typhoon-induced waves in their formation. This case study highlights the role of typhoons in influencing the formation of tropopause cirrus clouds through stratospheric hydration and waves.